Application of Starch in Modifying Acrylate Latex. Issue 2 (May 2016) - Xu, Tingting; Zhang, Cuifeng; Bao, Zhongbin; Chen, Lijun
The acrylate latex was a kind of production of emulsion polymerization of acrylate or methyl acrylate and other vinyl ester monomers. Starch was a biomaterial which found multiple applications in various branches. Novel approach to acrylate latex manufacture implied usage of composites e.g. the acrylate latex was being doped with starch to improve its properties and create biofriendly, naturally degrading material, and diminishing negative effect of polymeric waste production. In this paper, two methods that acrylate latex modified with starch are reviewed and summarized. The aim of the review is that provides the reference for use of the starch in modifying the acrylate latex.